2021
DOI: 10.5194/tc-15-3975-2021
|View full text |Cite
|
Sign up to set email alerts
|

Ground-penetrating radar imaging reveals glacier's drainage network in 3D

Abstract: Abstract. Hydrological systems of glaciers have a direct impact on the glacier dynamics. Since the 1950s, geophysical studies have provided insights into these hydrological systems. Unfortunately, such studies were predominantly conducted using 2D acquisitions along a few profiles, thus failing to provide spatially unaliased 3D images of englacial and subglacial water pathways. The latter has likely resulted in flawed constraints for the hydrological modelling of glacier drainage networks. Here, we present 3D … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 69 publications
(86 reference statements)
1
14
0
Order By: Relevance
“…Theoretical calculations using Hooke (1984) (Section S3.1 in Supporting Information S1) suggest a closure rate of 0.18 m per year if we assume a 5-m-diameter semi-circular channel. One explanation for a higher closure rate than predicted by theory is the deviation of the channel from a semi-circular shape, as observed in boreholes made at the Glacier d'Otemma during the summer of 2021, and reported for the Rhonegletscher by Church et al (2021). An analysis using the theory for non-semi-circular conduits by Hooke et al (1990) produces closure rate estimates over a 16-day period of ∼0.03-0.13 m (Section S3.5 in Supporting Information S1), which is commensurate with our estimations.…”
Section: Discussionmentioning
confidence: 82%
“…Theoretical calculations using Hooke (1984) (Section S3.1 in Supporting Information S1) suggest a closure rate of 0.18 m per year if we assume a 5-m-diameter semi-circular channel. One explanation for a higher closure rate than predicted by theory is the deviation of the channel from a semi-circular shape, as observed in boreholes made at the Glacier d'Otemma during the summer of 2021, and reported for the Rhonegletscher by Church et al (2021). An analysis using the theory for non-semi-circular conduits by Hooke et al (1990) produces closure rate estimates over a 16-day period of ∼0.03-0.13 m (Section S3.5 in Supporting Information S1), which is commensurate with our estimations.…”
Section: Discussionmentioning
confidence: 82%
“…Of special interest within glaciology is also the comparison of our method with the currently most commonly used method to localize glacial drainage systems: GPR. Most recently Church et al (2020) reconstructed an englacial channel on Rhonegletscher in Switzerland, both in 2D (Church et al, 2020) and in 3D (Church et al, 2021). In their 2020 study, Church et al (2020) reported a length error of 2.4 % (6 m) for a 250 m long englacial channel.…”
Section: Comparison With Gpr Perspectives and Limitationsmentioning
confidence: 99%
“…This indicates that the error in our method scales with the length of the investigated channel, thus resulting in a similar length error as reported for the GPR investigations by Church et al (2020) if scaled down to similar shorter channel length. However, our method only allows for reconstructing the actual water flow path and can currently not be used to infer information about channel width and height, as is possible with GPR (e.g., Stuart et al, 2003;Church et al, 2020Church et al, , 2021. The application of our drifter-based approach, in comparison to GPR, is further limited by a certain minimum needed discharge in combination with sufficient drainage system size for drifters to pass through, thus limiting the applicability to the main part of the melt season and channelized drainage systems.…”
Section: Comparison With Gpr Perspectives and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these in situ measurement techniques, remote geophysical methods have been used to infer properties of glacier drainage systems by radar and seismic imaging (e.g. Harper and others, 2010; Schroeder and others, 2013; Church and others, 2019, 2021; Egli and others, 2021) or by passively measuring seismic noise (e.g. Dalban Canassy and others, 2016; Gimbert and others, 2016; Röösli and others, 2016; Nanni and others, 2020).…”
Section: Introductionmentioning
confidence: 99%